2012
DOI: 10.1586/eri.12.74
|View full text |Cite
|
Sign up to set email alerts
|

Candida parapsilosisand the neonate: epidemiology, virulence and host defense in a unique patient setting

Abstract: Invasive candidiasis is a common problem in premature infants that leads to high morbidity and mortality. Although Candida albicans has historically been the most prominent species involved in these infections and has therefore been the subject of the most study, Candida parapsilosis is increasing in frequency, and neonates are disproportionately affected. This article reviews unique aspects of the epidemiology of this organism as well as strategies for prophylaxis against invasive candidiasis in general. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 110 publications
(128 reference statements)
2
35
0
5
Order By: Relevance
“…To expand our knowledge about the role of fungal eicosanoids in pathogenesis, we examined lipid mediator production in another important human fungal pathogen, C. parapsilosis . As the incidence of this species has increased over the past two decades and the patient group at risk includes immunosuppressed children and adults as well as neonates, understanding the pathogenesis of C. parapsilosis has gained increased attention [16,28]. Preliminary studies have started to elucidate the prostaglandin profile of this species [17], however, the involved biosynthetic pathways and the presence or role of other fungal eicosanoids remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…To expand our knowledge about the role of fungal eicosanoids in pathogenesis, we examined lipid mediator production in another important human fungal pathogen, C. parapsilosis . As the incidence of this species has increased over the past two decades and the patient group at risk includes immunosuppressed children and adults as well as neonates, understanding the pathogenesis of C. parapsilosis has gained increased attention [16,28]. Preliminary studies have started to elucidate the prostaglandin profile of this species [17], however, the involved biosynthetic pathways and the presence or role of other fungal eicosanoids remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have further reported C. parapsilosis to be the predominant species causing neonatal infections at intensive care units (ICU), threatening especially low birth weight infants, with significant neonatal mortality [7,[22][23][24]. Additionally, diverse adult patients with diminished immunity are also at risk [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports and previous reviews have already demonstrated the role of C. parapsilosis in nosocomial infections [23,24,29,36]. In this review, we aim to provide a description of a critically important effector protein of C. parapsilosis that has been proven to promote invasion, including altering host immune responses to the benefit of the fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Candida albicans was the most frequent cause of these infections, accounting for 70 to 80% of isolates from infected patients (5). However, infections caused by non-albicans Candida species, including C. glabrata and C. parapsilosis, are increasing in frequency worldwide (6)(7)(8). In some centers, C. parapsilosis has emerged as the leading cause of invasive candidiasis, particularly in newborns (9,10).…”
mentioning
confidence: 99%